(untitled) (Research, Society and Development, 2024)
The expert accounting is the instrument of verification that helps the judge in ascertaining facts to the equity, with the purpose of a correct and legitimate judgment. When performing an accounting inspection, it is necessary to consider the effects that the same causes to those involved, in order to be fair and honest, and even though, in several occasions, the judge’s decision is guided by the accountant’s work. In this context, the general objective of the work is to understand how the performance of the accounting expertise helps in solving the demands of legal proceedings, and the specific objectives are: to describe the performance of experts in the processes; present practices of an expert’s performance in a labor process; point out contributions to the assistance of lawsuits from the perspective of a labor accounting expertise. To achieve the objectives proposed in the study, a bibliographic review was used, with its main sources being books and scientific articles by authors who focused on the topic. In addition, a descriptive research was used, in order to describe the characteristics of a phenomenon. Therefore, this study shows that the greater the effectiveness of expert work procedures, the greater the added value of the expertise to the court decision.